Reproductive performance of lambari (Astyanax altiparanae) in a seminatural system using different protocols - Roza de Abreu, Mariana [UNESP]; Silva, Laíza Maria de Jesus [UNESP]; Figueiredo-Ariki, Daniel Guimarães [UNESP]; Sato, Rafael Tomoda [UNESP]; Kuradomi, Rafael Yutaka [UNESP]; Batlouni, Sergio Ricardo [UNESP] (Hindawi, 2021)
We evaluated lambari (Astyanax altiparanae) reproductive performance by administration of gradually increasing doses of analogue of salmon gonadotropin-releasing hormone (sGnRHa). We performed two consecutive experiments applying six sGnRHa single doses in three replicates (ranging from 1 to 160 µg/kg) (Exp. 1) and three sGnRHa-fractioned doses in four replicates (10% + 90% – 12 hr interval) (10, 100 and 1,000 µg/kg) (Exp. 2) in 6 months old breeders. In both experiments, 6 mg of Carp pituitary extract (CPE)/kg and saline solution (without hormonal therapy) were used as positive and negative controls, respectively. Reproductive performance was recorded for both experiments; and quantification of 17α-20β-dihydroxy-4-pregnen-3-one (17,20β-P) and prostaglandin F2α plasma levels and ovarian histological evaluations were introduced in Exp. 2. Using a single dose, the spawning rate was low and similar between all groups (from 0% to 20%). Using fractioned doses, the spawning rate of CPE (60%) was higher than other groups (from 10% to 25%), but similar to 1,000 µg of sGnRHa/kg (40%). 17,20β-P increased at the final sampling regardless of treatment (including controls) or successful spawning, suggesting that the simple grouping of fish caused this increase. 17,20β-P and PGF2α plasma levels did not explain ovulation failures in this species. CPE-fractioned doses improved lambari ovulation and provided final maturation in all evaluated females; however, hormonal induction was not conditional for obtaining ovulation since spawning was registered in negative control. Concluding, CPE-fractioned doses protocol can be applied to increase reproductive performance of this species.
Keywords: brood-stock management; controlled reproduction; egg maturation and ovulation; ovarian development; prostaglandin; sex steroids hormones